A solvent-free polymer adhesive film and its preparation process and prepared composite backplane
By optimizing the preparation process and raw material selection of polymer films, combined with thermal composite integrated molding technology, the problems of insufficient aging resistance and environmental pollution of the photovoltaic backplane are solved, and efficient and environmentally friendly photovoltaic backplane preparation is achieved.
Patent Information
- Application Number
- CN202310103697.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-13
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-02-13
AI Technical Summary
The aging resistance of existing photovoltaic back panels is insufficient, and traditional solvent-based adhesives will cause environmental pollution during the preparation process.
A solvent-free polymer film is used to prepare a high-temperature and water-resistant film by optimizing the raw material selection and preparation process, and a composite back plate is prepared through thermal composite integrated molding technology.
It improves the aging resistance and bonding properties of the photovoltaic backplane, maintains stability under ultraviolet, high temperature and high humidity conditions, and avoids the pollution of the environment by organic solvents.
Smart Images

Figure BDA0004074029420000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of membrane technology (IPC classification number is B32B27 / 08), and in particular to a solvent-free polymer adhesive film, a preparation process thereof and a composite backplane prepared therefrom. Background Art
[0002] Composite photovoltaic backsheets are the most commonly used photovoltaic backsheets on the market due to the good insulation and weather resistance of the fluorine film on the surface. However, their aging resistance seriously restricts the service life of photovoltaic backsheets. The main reason is that the adhesive between the fluorine film and the PET film is easily affected by the environment and ages and loses adhesion, causing the photovoltaic backsheet to lose its protective function.
[0003] At the same time, countries have increasingly stringent requirements for environmental protection. During the preparation of photovoltaic backsheets, organic solvents in traditional solvent-based adhesives will evaporate into the environment, causing environmental pollution. Therefore, a solvent-free adhesive with good aging resistance, weather resistance and bonding properties has become a trend in the industry.
[0004] Prior art CN113135010A discloses a method and system for preparing a solar photovoltaic back panel, which uses a solvent-free adhesive to bond a fluorine film to PET through composite roller lamination and winding, and has excellent bonding performance. However, the thin adhesive cannot ensure that the photovoltaic back panel can maintain its bonding performance during many years of long-term use.
[0005] In order to solve the above problems, the present invention provides a solvent-free polymer film and a composite backplane prepared therefrom. By optimizing the selection of raw materials and the preparation process, no organic solvent needs to be added during the preparation of the film, thus avoiding the environmental pollution caused by the volatilization of organic solvents. The prepared polymer film has good high temperature resistance and water resistance, strong bonding performance, and the composite backplane prepared therefrom has strong aging resistance and can still maintain excellent stability under ultraviolet, high temperature and high humidity conditions. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present invention provides a solvent-free polymer film, and its preparation raw materials include, by weight: 100 parts of polyester resin, 50-60 parts of tackifier, 30-60 parts of compatibilizer, 20-50 parts of high temperature modifier, 3-5 parts of anti-aging agent, 3-6 parts of ultraviolet absorber, and 2-7 parts of filler.
[0007] Preferably, the polyester resin is a modified self-made polyester resin, and the modification method is to modify the self-made polyester resin with acrylic resin.
[0008] Preferably, the self-made polyester resin is obtained by polycondensation of a dicarboxylic acid with any one or at least two of a diol, a diphenol, a diester or a compound containing an ethylene oxide group.
[0009] Preferably, the dicarboxylic acid is at least one selected from adipic acid, azelaic acid, sebacic anhydride, isophthalic acid, terephthalic acid, and dimethyl terephthalate.
[0010] Preferably, the diol is selected from at least one of ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, pentylene glycol, diethylene glycol and dipropylene glycol.
[0011] Preferably, the dihydric phenol is selected from at least one of catechol, resorcinol and hydroquinone.
[0012] Preferably, the raw materials of the self-made polyester resin include adipic acid, isophthalic acid, butyl glycol, and 2-butene-diol.
[0013] Preferably, the weight ratio of the dicarboxylic acid to the diol is (11-17):10.
[0014] Preferably, the raw material of the polymer film further includes a free radical initiator.
[0015] Preferably, the free radical initiator is a peroxidation initiator.
[0016] Preferably, the acrylic resin is a thermoplastic resin.
[0017] Preferably, the weight ratio of the self-made polyester resin to the acrylic resin is 1:(0.3-1).
[0018] The applicant found that when the polyester resin is a homemade polyester resin modified by acrylic acid, the homemade polyester resin is a prepolymer formed by polymerization of adipic acid, isophthalic acid, butyl glycol, and 2-butene-diol, and the weight ratio of the homemade polyester resin to the acrylic resin is 1: (0.3-1), the prepared polymer adhesive film has a good initial bonding effect on the backboard of PET material, and has good high temperature resistance, can be used at higher processing temperatures, and has good water resistance and solvent resistance. The applicant found in the experimental process that using the homemade polyester resin modified by acrylic acid as the matrix can increase the initial bonding effect of the adhesive and the PET film material, and when the weight ratio of the homemade polyester resin to the acrylic resin is 1: (0.3-1), the formed adhesive has good high temperature resistance and can adapt to processing temperatures above 120°C. The possible reasons are speculated to be: the use of adipic acid and isophthalic acid as raw materials for the preparation of homemade polyester resins can make the polarity of homemade polyester resins relatively low due to the longer chain length of the molecular structure, and the wetting effect on PET film materials is better, so that it has good initial adhesion, and the applicant has further found that polyester adhesives with low polarity have poor binding properties with water, thus having good water resistance. However, the use of simple homemade polyester resins as adhesives has low adhesion, and the introduction of acrylic resin modification can improve the adhesive. When the weight ratio of homemade polyester resin to acrylic resin is 1: (0.3-1), a tightly cross-linked network can be formed between the homemade polyester resin and the acrylic resin, which improves the cohesive force of the adhesive, thereby improving the adhesive's holding force and the bonding effect. Exceeding the preferred weight ratio range will cause the glass transition temperature to drop, affecting the high temperature resistance of the adhesive.
[0019] Preferably, the tackifier is selected from at least one of rosin resins, polyterpene resins, dammar resins, petroleum resins, coumarone-indene resins, and polystyrene resins.
[0020] Preferably, the tackifier is hydrogenated rosin resin.
[0021] Preferably, the compatibilizer is selected from at least one of a silane coupling agent, an epoxy resin, a phenolic resin, and an acid anhydride.
[0022] Preferably, the compatibilizer is phenolic resin.
[0023] Preferably, the high temperature modifier is selected from at least one of acrylate, silicone oil and hydroxynaphthalene.
[0024] Preferably, the high temperature modifier is hydroxynaphthalene.
[0025] Preferably, the weight ratio of the polyester resin to hydroxynaphthalene is 10:(2-5).
[0026] The applicant found that when the high-temperature modifier is hydroxynaphthalene and the weight ratio of polyester resin to hydroxynaphthalene is 10:(2-5), the heat resistance of the adhesive film is improved, and the adhesive film has a good bonding effect with both the PET film material and the fluorine film. The formed adhesive film has good cohesion, and the hydroxynaphthalene is not easy to migrate out, and the performance is stable and the service life is long. BIPV integrated photovoltaic buildings use polymer materials as bonding layers, and are integrated with PET film materials and fluorine films through thermal composite molding. During the experiment, the applicant found that the adhesives on the market have poor bonding effects on fluorine films. The applicant creatively found that by introducing hydroxynaphthalene into the adhesive raw materials, the bonding effect between the adhesive and the fluorine film can be improved. The possible reason is guessed to be: the introduction of hydroxynaphthalene, the naphthalene ring has a larger conjugated double bond than the benzene ring, which improves the non-polarity of the adhesive film, thereby generating good intermolecular forces with the fluorine film, thereby improving the overall bonding performance of the adhesive film to the fluorine film and PET film. The applicant further discovered that the hydroxyl group in hydroxynaphthalene can react with the carboxyl group in the polyester resin, and the hydroxynaphthalene is connected to the film matrix through a chemical bond, which can prevent the migration of hydroxynaphthalene, maintain the structural stability of the film, and extend the service life. At the same time, the introduction of hydroxynaphthalene further improves the high temperature resistance of the film, making it have good high temperature processing performance.
[0027] Preferably, the filler is selected from at least one of calcium carbonate, montmorillonite, kaolin, mica powder, talc powder and titanium dioxide.
[0028] Preferably, the filler is a combination of montmorillonite and titanium dioxide, and the weight ratio of montmorillonite to titanium dioxide is (1-3): (1-4).
[0029] The type of the anti-aging agent described in the present invention is not particularly limited, and the antioxidant BHT is preferred.
[0030] The type of the ultraviolet absorber described in the present invention is not particularly limited, and is preferably an ultraviolet absorber UV-P.
[0031] The second aspect of the present invention provides a process for preparing a solvent-free polymer film, comprising the following steps:
[0032] S1, adding any one or at least two compounds of dicarboxylic acid, diol, diphenol, dibasic ester or compound containing ethylene oxide group into a reaction kettle and heating and polycondensing to obtain a self-made polyester resin;
[0033] S2, adding acrylic resin and free radical initiator to the self-made polyester resin and heating and stirring to obtain polyester resin;
[0034] S3, adding a tackifier, a compatibilizer, and a high temperature modifier to the polyester resin and mixing them at a high temperature;
[0035] S4, adding an anti-aging agent, a UV absorber, montmorillonite, and titanium dioxide, and mixing and stirring for 1-3 hours to obtain a mixture;
[0036] S5. Extruding the mixture through a screw machine, controlling the film thickness to be 50-70 μm, to obtain a polymer film.
[0037] Preferably, in step S1, the reaction temperature is adjusted to 80-90° C. and the reaction time is 3-4 h.
[0038] Preferably, in step S2, the reaction temperature is adjusted to 90-120° C. and the reaction time is 2-3 h.
[0039] Preferably, in step S3, the reaction temperature is adjusted to 120-140° C. and the reaction time is 1-2 h.
[0040] Preferably, in step S5, the extrusion temperature is adjusted to 180-200°C.
[0041] Another aspect of the present invention provides a composite backplane prepared from a solvent-free polymer film, the structure of which from top to bottom is a fluorine film, a polymer film, a PET film material, a polymer film, and a fluorine film.
[0042] Preferably, the type of the fluorine film is not particularly limited, and is preferably a vinylidene fluoride film with a single layer thickness of 25-30 μm.
[0043] Preferably, the thickness of the PET film is 250-300 μm.
[0044] The third aspect of the present invention provides a composite backplane prepared by a solvent-free polymer film, and the preparation process thereof is as follows:
[0045] The fluorine film, polymer film, PET film, polymer film and fluorine film are stacked in sequence and pressed at high temperature to prepare a composite backplane.
[0046] Preferably, in the high-temperature pressing operation, the pressure is adjusted to 10-100 MPa, the pressing temperature is 120-130° C., and the pressing time is 0.1-0.5 h.
[0047] Beneficial Effects
[0048] 1. A self-made polyester resin is prepared by selecting adipic acid, isophthalic acid, butyl glycol and 2-butene-diol as raw materials, so that the prepared polymer film has a good initial bonding effect on the PET backplane, and has good water resistance and solvent resistance.
[0049] 2. By limiting the weight ratio of homemade polyester resin to acrylic resin to 1: (0.3-1), an acrylic resin-modified homemade polyester resin is obtained, so that the prepared polymer film has good high temperature resistance, can be used at higher processing temperatures, and improves the adhesion effect on the PET backplane.
[0050] 3. By limiting the high-temperature modifier to hydroxynaphthalene, the heat resistance of the film is improved, and the film has a good bonding effect with the PET film and the fluorine film, and the formed film has good cohesion.
[0051] 4. By limiting the weight ratio of polyester resin to hydroxynaphthalene to 10:(2-5), hydroxynaphthalene is not easy to migrate out, the film performance is stable, and the service life is long.
[0052] 5. By optimizing the selection of raw materials and the preparation process, it is not necessary to add organic solvents during the preparation of the film, thus avoiding the environmental pollution caused by the volatilization of organic solvents. DETAILED DESCRIPTION
[0053] Example
[0054] Example 1
[0055] Example 1 provides a solvent-free polymer film, and its preparation raw materials include, by weight: 20 parts of adipic acid, 20 parts of isophthalic acid, 14 parts of butyl glycol, 12 parts of 2-butene-diol, 9 parts of free radical initiator, 25 parts of acrylic resin, 55 parts of hydrogenated rosin resin, 40 parts of phenolic resin, 30 parts of hydroxynaphthalene, 3 parts of antioxidant, 5 parts of ultraviolet absorber, 2 parts of titanium dioxide, and 2 parts of montmorillonite.
[0056] The adipic acid is produced from Liaoyang Petrochemical.
[0057] The isophthalic acid is produced from Mitsubishi of Japan.
[0058] The butyl glycol was produced by Dow.
[0059] The 2-butene-diol is produced from the Wengjiang reagent.
[0060] The free radical initiator is benzoyl peroxide, produced by Shanghai Guoyao.
[0061] The acrylic resin is a thermoplastic acrylic resin selected from CBS-10 acrylic resin produced by Shantou Acrylic Polymer Resin Factory.
[0062] The hydrogenated rosin resin is selected from Eastman Chemical's 5020-F hydrogenated rosin resin.
[0063] The phenolic resin is selected from the SP-1068 phenolic resin of SI Group.
[0064] The hydroxynaphthalene is selected from D822878 type 1,6-dihydroxynaphthalene of MacLean reagent.
[0065] The anti-aging agent is the antioxidant BHT, produced by Jihong Chemical.
[0066] The ultraviolet absorber is ultraviolet absorber UV-P, which is produced by Foshan Jingding Plastic Chemical Co., Ltd.
[0067] The titanium dioxide is selected from BA-6B titanium dioxide produced by Foshan Jingding Plastic Chemical Co., Ltd.
[0068] The montmorillonite is selected from DK1 montmorillonite produced by Zhejiang Fenghong New Materials Co., Ltd.
[0069] A process for preparing a solvent-free polymer film comprises the following steps:
[0070] S1, adding adipic acid, isophthalic acid, butyl glycol, and 2-butene-diol into a reaction kettle, evacuating and filling with nitrogen, heating to 85°C for 4 hours to polycondense, and obtaining a self-made polyester resin;
[0071] S2, adding 9 parts of acrylic resin and benzoyl peroxide to the self-made polyester resin, heating to 100° C. and stirring for 2 h to obtain a polyester resin;
[0072] S3, adding hydrogenated rosin resin, phenolic resin and hydroxy naphthalene to polyester resin, heating to 130°C and blending for 1 hour;
[0073] S4, adding antioxidant BHT, ultraviolet absorber UV-P, montmorillonite, and titanium dioxide, mixing and stirring for 2 hours to obtain a mixture;
[0074] S5. Cast and extrude the mixture through a screw machine at 180° C., control the film thickness to be 60 μm, and obtain a polymer film.
[0075] Example 1 provides a composite backplane prepared from a solvent-free polymer film, the structure of which from top to bottom is a fluorine film, a polymer film, a PET film material, a polymer film, and a fluorine film.
[0076] The fluorine film is a vinylidene fluoride film purchased from Hangzhou Fumo New Material Technology Co., Ltd.
[0077] The PET film material was purchased from Shenzhen Bangli Adhesive Products Co., Ltd., and the model is Toray H10.
[0078] A preparation process of a composite backplane made of a solvent-free polymer film is as follows:
[0079] A 30 μm vinylidene fluoride film, a 60 μm polymer adhesive film, a 280 μm PET film, a 60 μm polymer adhesive film, and a 30 μm vinylidene fluoride film are stacked in sequence, pressed at 125° C. using a laminator to prepare a new composite backplane.
[0080] Comparative Example 1
[0081] A solvent-free polymer adhesive film, a preparation process thereof and a composite backplane prepared therefrom. The implementation method of comparative example 1 is the same as that of example 1; the difference is that in comparative example 1, no isophthalic acid is added, but 40 parts of adipic acid are added.
[0082] Comparative Example 2
[0083] A solvent-free polymer adhesive film, a preparation process thereof and a composite backplane prepared therefrom. The implementation method of comparative example 2 is the same as that of example 1; the difference is that 10 parts of adipic acid, 10 parts of isophthalic acid, 7 parts of butyl glycol, 6 parts of 2-butene-diol and 58 parts of acrylic resin are added to comparative example 2.
[0084] Comparative Example 3
[0085] A solvent-free polymer adhesive film, a preparation process thereof and a composite backplane prepared therefrom, wherein the implementation method of comparative example 3 is the same as that of example 1; the difference is that in comparative example 3, 28 parts of adipic acid, 27 parts of isophthalic acid, 18 parts of butyl glycol and 18 parts of 2-butene-diol are added, and no acrylic resin is added.
[0086] Comparative Example 4
[0087] A solvent-free polymer adhesive film, a preparation process thereof and a composite backplane prepared therefrom. The implementation method of comparative example 4 is the same as that of example 1; the difference is that in comparative example 4, 30 parts of silicone oil are added as a high-temperature modifier, and hydroxynaphthalene is not added.
[0088] The silicone oil is selected from KF-965-100CS dimethyl silicone oil produced by Shin-Etsu of Japan.
[0089] Comparative Example 5
[0090] A solvent-free polymer adhesive film, a preparation process thereof and a composite backplane prepared therefrom. The implementation method of comparative example 5 is the same as that of example 1; the difference is that 60 parts of hydroxynaphthalene are added in comparative example 5.
[0091] Performance Testing Methods
[0092] The composite backsheets prepared in Example 1 and Comparative Examples 1-5 were cut into a size of 200 mm*10 mm, and the 180° peel strength test was performed between the polymer film and the PET film under room temperature, UV aging, and wet heat aging conditions according to the method in "Backsheet for Photovoltaic Modules" (SJ / T 11722-2018). The test results are shown in Table 1.
[0093] Table 1 Performance test results
[0094]
[0095] Initial adhesion is the interlayer peeling strength at room temperature. After performance testing, the composite backsheet of the present invention meets the use conditions of photovoltaic module backsheets, meets the requirements of ≥2.5N / cm after UV aging test, and meets the requirements of greater than 2.0N / cm after wet heat aging.
Claims
1. A solvent-free polymer film, characterized in that: The raw materials for its preparation include: 100 parts of polyester resin, 50-60 parts of tackifier, 30-60 parts of compatibilizer, 20-50 parts of high temperature modifier, 3-5 parts of anti-aging agent, 3-6 parts of ultraviolet absorber, and 2-7 parts of filler; The polyester resin is a modified self-made polyester resin, and the modification method is to modify the self-made polyester resin with acrylic resin; The self-made polyester resin is a prepolymer obtained by polymerization of adipic acid, isophthalic acid, butyl glycol and 2-butene-diol; The weight ratio of dicarboxylic acid to diol is (11-17): 10; The weight ratio of the self-made polyester resin to the acrylic resin is 1:(0.3-1); The high temperature modifier is hydroxynaphthalene, and the weight ratio of the polyester resin to the hydroxynaphthalene is 10:(2-5).
2. The solvent-free polymer film according to claim 1, characterized in that: The raw materials of the polymer film also include a free radical initiator.
3. The solvent-free polymer film according to claim 2, characterized in that: The free radical initiator is a peroxidation initiator.
4. The solvent-free polymer film according to claim 1, characterized in that: The tackifier is selected from at least one of rosin resins, polyterpene resins, dammar resins, petroleum resins, coumarone-indene resins, and polystyrene resins.
5. The solvent-free polymer film according to claim 1, characterized in that: The compatibilizer is selected from at least one of a silane coupling agent, an epoxy resin, a phenolic resin, and an acid anhydride.
6. A process for preparing a solvent-free polymer film according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, adding adipic acid, isophthalic acid, butyl glycol, and 2-butene-diol into a reaction kettle and heating and polycondensing to obtain a self-made polyester resin; S2, adding acrylic resin and free radical initiator to the self-made polyester resin and heating and stirring to obtain polyester resin; S3, adding a tackifier, a compatibilizer, and a high temperature modifier to the polyester resin and mixing them at a high temperature; S4, adding an anti-aging agent, a UV absorber, montmorillonite, and titanium dioxide, and mixing and stirring for 1-3 hours to obtain a mixture; S5. Extruding the mixture through a screw machine, controlling the film thickness to be 50-70 μm, to obtain a polymer film.
7. A composite back sheet made of a solvent-free polymer film according to claim 1, characterized in that: Its structure from top to bottom is fluorine film, polymer film, PET film material, polymer film, and fluorine film.
Citation Information
Patent Citations
Preparation method and preparation system of solar photovoltaic backboard
CN113135010A
Solar cell back plate membrane and preparation method thereof
CN103921519A
Polyester-based primer composition, optical film using same and polarizing plate comprising same
CN104284938A
Adhesive, preparation method and application, sticky adhesive tape containing adhesive and preparation method of sticky adhesive tape
CN108977153A